Integrative multi-omic profiling of the chronically hypoxic heart: focus on m6A and m6Am epitranscriptomic regulation - Hlavackova, Marketa; Benak, Daniel; Sotakova-Kasparova, Dita; Holzerova, Kristyna; Skriba, Anton; Simonova, Anna; Cahova, Hana; Kobets, Tatyana; Jancova, Tereza; Kolar, Frantisek (Frontiers in Cell and Developmental Biology, 2026)
Reduced oxygen availability is an environmental factor characteristic of high-altitude conditions that plays a critical role in shaping cellular homeostasis and epigenomic regulation. Adaptation to various models of chronic hypoxia represents a well-recognized physiological process that enhances cardiac tolerance to ischemic stress; however, the molecular mechanisms coordinating metabolic, proteomic, and post-transcriptional remodeling in this adaptive response to low-oxygen conditions remain insufficiently understood. Here, we combined quantitative metabolomic, lipidomic, and proteomic profiling with targeted protein analyses to characterize the molecular landscape of rat hearts adapted to continuous normobaric hypoxia (CNH, 10% O2 for 3 weeks). Multi-omics integration revealed tightly coupled remodeling across metabolic and structural domains, consistent with enhanced energetic efficiency and oxidative stress resistance. Pathway enrichment identified coordinated activation of energy reprogramming (AMPK, glycolysis, and PPAR signaling), reinforcement of antioxidant defense (glutathione metabolism), membrane remodeling (glycerophospholipid and peroxisomal pathways), and protein quality control (autophagy–lysosome and proteasome systems). Beyond these canonical adaptive responses, CNH markedly affected the epitranscriptomic machinery: both m6A demethylases ALKBH5 and FTO – enzymes previously linked to cardioprotective effects – were upregulated, accompanied by increased abundance of multiple m6A readers (YTHDF1–3, YTHDC1), whereas methyltransferases METTL3 and PCIF1 remained stable. At the level of RNA modifications, global m6A levels in total RNA were unchanged, whereas m6Am levels were significantly increased under hypoxia. These results demonstrate that chronic hypoxia reprograms the heart not only at the metabolic and proteomic levels but also through epitranscriptomic regulation, suggesting that RNA methylation dynamics may contribute to the cardioprotective phenotype. Collectively, our findings provide a system-level framework linking metabolic flexibility, redox balance, and post-transcriptional control during hypoxic adaptation.